Pseudomonas fluorescens Cells’ Recovery after Exposure to BAC and DBNPA Biocides - Ana C. Barros; Luis F. Melo; Ana Pereira (Antibiotics, 2022)
A proper assessment of the effects of biocides on bacterial cells is key to the prevention of antimicrobial resistance and the implementation of suitable biocidal programmes. It is particularly relevant regarding the ability of dead-labelled cells to recover their functional processes once the biocide is removed. In the present work, we studied how Pseudomonas fluorescens cells previously exposed to different concentrations of BAC (benzalkonium chloride) and DBNPA (2,2-Dibromo-3-nitrilopropionamide) behave upon the restoration of optimum growth conditions. The following indicators were evaluated: culturability, membrane integrity, metabolic activity (resazurin), cellular energy (ATP), and cell structure and morphology (transmission electron microscopy (TEM)). The results demonstrated that cells previously labelled as ‘dead’ recovered to a greater extent in all indicators. Only cells previously exposed to BAC at 160 mg/L (concentration above the MBC) showed significant reductions on all the evaluated indicators. However, the obtained values were much higher than the ‘death’ thresholds found for the autoclaved cells. This suggests that cells exposed to this concentration take more time to rebuild their functional processes. The recovery of DBNPA-treated cells did not seem to be related to the biocide concentration. Finally, a reflection on what kind of cells were able to recover (remaining cells below the detection limit and/or dormant cells) is also presented.